Sex differences in the incidence and mode of death in rats with heart failure with preserved ejection fraction. Issue 3 (19th January 2021) - Elkholey, Khaled; Morris, Lynsie; Niewiadomska, Monika; Houser, Jeremy; Ramirez, Michelle; Tang, Mulan; Humphrey, Mary Beth; Stavrakis, Stavros
Abstract : New Findings: What is the central question of this study? Prior studies failed to address the role of sex in modifying the pathophysiology and response to therapy in heart failure with preserved ejection fraction (HFpEF), potentially introducing bias into translational findings. We aimed to explore sex differences in outcomes and sought to identify the underlying mechanisms in a well‐established rat model of HFpEF. What is the main finding and its importance? Male rats with HFpEF exhibited worse survival compared with females and were at a higher risk for sudden death, attributable in part to QT prolongation, autonomic dysregulation and enhanced inflammation. These data might provide the basis for the development of sex‐specific interventions in HFpEF targeting these abnormalities. Abstract: Heart failure with preserved ejection fraction (HFpEF) accounts for 50% of heart failure, and sudden death is the leading cause of mortality. We aimed to explore sex differences in outcomes in rats with HFpEF and sought to identify the underlying mechanisms. Dahl salt‐sensitive rats of either sex were randomized into high‐salt diet (HS diet; 8% NaCl, n  = 46, 50% female) or low‐salt diet (LS diet; 0.3% NaCl; n  = 24, 50% female) at 7 weeks of age. After 6 and 10 weeks of LS or HS diets, the ECG, heart rate variability, cytokines and echocardiographic parameters were measured. The animals were monitored daily for development of HFpEF and survival. Over 6 weeks of HS diet, rats developed significant hypertension and signs of HFpEF. Compared with female HS diet‐fed rats, males exhibited more left ventricular dilatation, a longer QT interval, and worse autonomic tone, as assessed by heart rate variability and elevated inflammatory cytokines. Ten of 23 (46%) male rats died during follow‐up, compared with two of 23 (9%) female rats ( P  = 0.01). There were four sudden deaths in males (with ventricular tachycardia documented in one rat), whereas the females died of heart failure. In conclusion, male rats with HFpEF exhibit worse survival compared with females and are at a higher risk for sudden death, attributable in part to QT prolongation, autonomic dysregulation and enhanced inflammation. These data might provide the basis for the development of sex‐specific interventions in HFpEF targeting these abnormalities. Abstract :